Floral characterization of some self-compatible almond selections - Kodad O.; Socias i Company R. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Bud density, bloom phenology, flower morphology, and pollen tube growth were studied in seven almond (Prunus amygdalus Batsch) selections of the Zaragoza breeding programme. Bud density varied and may be qualified from medium to high. Blooming time was late for all selections, the first flowers opened the third week of February, which helped avoiding frost damage until that time. Self-compatibility was confirmed in all selections and was assessed by their own pollen growth, reaching the base of the style in all cases. Furthermore, pollen tube growth was similar both after self- and cross-pollination. Genetic self-compatibility was also confirmed by the S-genotype of the selections, as determined by separation of the stylar S-RNases. The importance of the style is also shown by the effect of the style length on the pollen tube growth and the stigma-anther position inside the flower. The stigma position indicates the possibility of natural autogamy in two of the seven selections.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)